Pengaruh Karakteristik Direktur Utama terhadap Kinerja Karbon Perusahaan - Nugroho, Kenny Christony; Hasnawati, Hasnawati (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This research aims to examine the influence of the characteristics of the main director on the company's carbon performance. This research uses a population consisting of non-financial companies listed on the Indonesia Stock Exchange (BEI) in the 2019-2022 period. The data taken from this sample is secondary data in the form of information on company carbon emissions obtained through annual reports and sustainability reports for 2019-2022. Data was collected from 180 different companies with a final total sample of 350 data using purposive sampling techniques. Data processing was carried out using the SPSS 25 application and using the multiple linear regression method. Based on the analysis carried out, it was concluded that the characteristics of the main director in the form of tenure and level of education have a negative effect on the company's carbon emissions intensity. Characteristics such as the age of the main director have no effect on the company's carbon emissions intensity.